2016
DOI: 10.1093/nar/gkw544
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, base pairing and structure studies of geranylated RNA

Abstract: Natural RNAs utilize extensive chemical modifications to diversify their structures and functions. 2-Thiouridine geranylation is a special hydrophobic tRNA modification that has been discovered very recently in several bacteria, such as Escherichia coli, Enterobacter aerogenes, Pseudomonas aeruginosa and Salmonella Typhimurium. The geranylated residues are located in the first anticodon position of tRNAs specific for lysine, glutamine and glutamic acid. This big hydrophobic terpene functional group affects the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…This hydrophobic geranyl group has been known to affect codon recognition and frameshifting during translation (Dumelin et al, 2012). In previous studies, both the 2 -deoxy-and ribo-versions of S-geranyluridine have been synthesized and the geranylated 2-thioT-G or 2-thioU-G pairs showed much stronger thermal stability than the corresponding T-A and other mismatched pairs in the DNA and RNA duplex contexts, which is consistent with the observation that the geranylated tRNA Glu UUC recognizes GAG more efficiently than GAA (Wang et al, 2015;Wang et al, 2016). This unit contributes the synthesis of geranylated 2-thiouridine Trimethylsilyl chloride (purified by redistillation, ࣙ99%, Sigma-Aldrich) 1-O-Acetyl-2,3,5-tri-O-benzoyl β-D-ribofuranose (99.5% pure, ChemGenes) 1,2-Dichloroethane (anhydrous, 99.8%, Sigma-Aldrich) NaCl (aqueous, saturated) Tin(IV) chloride (99.995% trace metals basis, Sigma-Aldrich) Saturated aqueous sodium bicarbonate (NaHCO 3 ) Methylene chloride (dichloromethane, CH 2 Cl 2 ; purity >99.5%, Fluka) Anhydrous magnesium sulfate (MgSO 4 ) Methanol (anhydrous MeOH, Sigma-Aldrich) Sodium methoxide (99.995% trace metals basis, Sigma-Aldrich) DOWEX 50WX8-400 ion-exchange resin (H + form) (Sigma-Aldrich) Ethyl acetate (EtOAc) Ethanol (absolute) N,N-Dimethylformamide (DMF; anhydrous, 99% pure, Sigma-Aldrich) Di-tert-butylsilyl bis(trifluoromethanesulfonate) (97%, Sigma-Aldrich) Imidazole (ACS reagent, ࣙ99%, Sigma-Aldrich) tert-Butyldimethylsilyl chloride (>97%, Sigma-Aldrich) HCl (aqueous, 1.0 M) Anhydrous sodium sulfate (Na 2 SO 4 ) Silica gel (60-Å porosity; 40-to 63-μm particle size; 400 mesh) HF-pyridine (ß30% pyridine/ß70% hydrogen fluoride, Sigma-Aldrich) Pyridine (anhydrous, purity >99%, Sigma-Aldrich) 4,4 -Dimethoxytrityl chloride (95%, Sigma-Aldrich) Triethylamine (>99%, Sigma-Aldrich) N,N-Diisopropylethylamine (DIPEA; 99% pure, Sigma-Aldrich) Geranyl bromide (95%, Sigma-Aldrich) 2-Cyanoethyl N,N-diisopropylchlorophosphoramidite (ChemGenes Corporation) 250-mL three-neck, round-bottom flasks, oven-dried Magnetic stir bars Reflux apparatus 250-mL one-neck, round-bottom flasks, oven-dried Rotary evaporator Vacuum oil pump 1-, 5-, and 10-mL syringes 1000-mL beakers Filter paper pH paper Lyophilizer 10-, 25-, 50-, and 100-mL round-bottom flasks Thermometer Hot plate Separatory funnels Rubber septum 22 × 457-mm silica gel chromatography columns Additional reagents and equipment for performing thin-layer chromatography (TLC) and column chromatography 3.…”
Section: Introductionsupporting
confidence: 81%
“…This hydrophobic geranyl group has been known to affect codon recognition and frameshifting during translation (Dumelin et al, 2012). In previous studies, both the 2 -deoxy-and ribo-versions of S-geranyluridine have been synthesized and the geranylated 2-thioT-G or 2-thioU-G pairs showed much stronger thermal stability than the corresponding T-A and other mismatched pairs in the DNA and RNA duplex contexts, which is consistent with the observation that the geranylated tRNA Glu UUC recognizes GAG more efficiently than GAA (Wang et al, 2015;Wang et al, 2016). This unit contributes the synthesis of geranylated 2-thiouridine Trimethylsilyl chloride (purified by redistillation, ࣙ99%, Sigma-Aldrich) 1-O-Acetyl-2,3,5-tri-O-benzoyl β-D-ribofuranose (99.5% pure, ChemGenes) 1,2-Dichloroethane (anhydrous, 99.8%, Sigma-Aldrich) NaCl (aqueous, saturated) Tin(IV) chloride (99.995% trace metals basis, Sigma-Aldrich) Saturated aqueous sodium bicarbonate (NaHCO 3 ) Methylene chloride (dichloromethane, CH 2 Cl 2 ; purity >99.5%, Fluka) Anhydrous magnesium sulfate (MgSO 4 ) Methanol (anhydrous MeOH, Sigma-Aldrich) Sodium methoxide (99.995% trace metals basis, Sigma-Aldrich) DOWEX 50WX8-400 ion-exchange resin (H + form) (Sigma-Aldrich) Ethyl acetate (EtOAc) Ethanol (absolute) N,N-Dimethylformamide (DMF; anhydrous, 99% pure, Sigma-Aldrich) Di-tert-butylsilyl bis(trifluoromethanesulfonate) (97%, Sigma-Aldrich) Imidazole (ACS reagent, ࣙ99%, Sigma-Aldrich) tert-Butyldimethylsilyl chloride (>97%, Sigma-Aldrich) HCl (aqueous, 1.0 M) Anhydrous sodium sulfate (Na 2 SO 4 ) Silica gel (60-Å porosity; 40-to 63-μm particle size; 400 mesh) HF-pyridine (ß30% pyridine/ß70% hydrogen fluoride, Sigma-Aldrich) Pyridine (anhydrous, purity >99%, Sigma-Aldrich) 4,4 -Dimethoxytrityl chloride (95%, Sigma-Aldrich) Triethylamine (>99%, Sigma-Aldrich) N,N-Diisopropylethylamine (DIPEA; 99% pure, Sigma-Aldrich) Geranyl bromide (95%, Sigma-Aldrich) 2-Cyanoethyl N,N-diisopropylchlorophosphoramidite (ChemGenes Corporation) 250-mL three-neck, round-bottom flasks, oven-dried Magnetic stir bars Reflux apparatus 250-mL one-neck, round-bottom flasks, oven-dried Rotary evaporator Vacuum oil pump 1-, 5-, and 10-mL syringes 1000-mL beakers Filter paper pH paper Lyophilizer 10-, 25-, 50-, and 100-mL round-bottom flasks Thermometer Hot plate Separatory funnels Rubber septum 22 × 457-mm silica gel chromatography columns Additional reagents and equipment for performing thin-layer chromatography (TLC) and column chromatography 3.…”
Section: Introductionsupporting
confidence: 81%
“…Three model 17‐nucleotide RNA oligomers of the sequence 5′‐GUUGACU X UUAAUCAAC‐3′, where X = S2U ( 1c ), Se2U ( 2c ), or geS2U ( 3c ) (Table ), encoded S2U‐RNA, geS2U‐RNA, and Se2U‐RNA, respectively, were prepared (as described earlier ) to help verify the hypothesis on the SelU‐promoted sequential transformation S2U‐RNA→geS2U‐RNA→Se2U‐RNA. The sequence was selected intentionally as the S2U‐RNA oligomer is iso ‐sequential with the anticodon‐stem‐loop fragment (ASL) of the bacterial tRNA specific for lysine (tRNA Lys ), and the modified units (X) occupy the site corresponding to the wobble position in transfer RNA.…”
Section: Resultsmentioning
confidence: 99%
“…Three model 17-nucleotide RNA oligomers of the sequence 5 0 -GUUGACU X UUAAUCAAC-3 0 , where X = S2U (1c), Se2U (2c), or geS2U (3c) ( Table 1), encoded S2U-RNA, geS2U-RNA, and Se2U-RNA, respectively, were prepared (as described earlier [10,21,22]) to help verify the hypothesis on the SelUpromoted sequential transformation S2U-RNA? geS2U-RNA?Se2U-RNA.…”
Section: Synthesis and Characteristics Of Rna Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both crystallographic and computational studies of the τ 5 mU 34 -modified ASL of mitochondrial tRNA Leu UAA have revealed stabilized hydrogen bonding interactions between the sulfonic acid and secondary amine moieties of the modification and nucleosides U 33 , A 35 and A 36 , as well as adoption of a non-Watson-Crick U 34 •G 3 geometry thought to enhance stacking [120,153]. Likewise, 2-thiouridine geranylation (Figure 2b) in bacteria facilitates tRNA Glu UUC and tRNA Lys UUU formation of stable Watson-Crick U 34 •G 3 wobble base pairs at the anticodon-codon interface [154,155]. The large hydrophobic terpene geranyl group covalently modifies the position 2 thio group of 2-thiouridine inducing a loss of protonation at the N3 atom of U 34 [156].…”
Section: Modifications At Position 34mentioning
confidence: 99%